SELF-MONITORING ANALYSIS RESULTS DATABASE DESIGN FOR WASTEWATER TREATMENT INSTALATION IN MANUFACTURING INDUSTRY PACKAGING CANS - Sulaeman, Oman; Setiadi, Imam (Jurnal Rekayasa Lingkungan, 2016)
In monitoring the environmental quality, besides it needs the data analysis also requires the presentation of accurate data so as to display an useful information. If the data is not immediately available it is feared worsening quality changes that will lead to difficulties in recovery. Self-monitoring analysis results database design for wastewater treatment instalation in manufacturing industry packaging cans aims to create a new procedure in terms of the storage and management to create a new procedure in termsof the storage and management of data replaces the old method is still conventional. Database design also features graphic user interface (GUI) as a medium for user interaction with the database software. Database database software is designed with the Logical database design method in which the process of making a model of the information used in the company based on the model-specific data, but does not depend on the Database Management System (DBMS). DBMS is a software that allows users to define, create, maintain, and control access to the database. Results to be achieved with the existence of this database is that users can easily perform datastorage, update the data, speed up retrieval of earlier data, and assist to present a report. Given this self-monitoring analysis results database, the data can be stored properly and safely on the database to be managed in the future as well as complementary data sources in reporting self-monitoring of wastewater treatment.keywords : self monitoring, database,DMBS, data update, and wastewater treatment plant